Niewidomi w kinie? Prawne wyzwania upowszechnienia audiodeskrypcji filmów w Polsce - Paluszek, Karolina (PRAWO i WIĘŹ, 2025)
This paper presents the legal aspects of the popularisation of audio description as a film adaptation (or, more precisely, the translation of its visual layer into a verbal one), which enables blind and visually impaired people to have access to cinematic art. The author analyses the legal definitions of audio description in Polish law, briefly describes the use of audio description in cinemas, and presents the copyright aspects of the issue. The elaboration of the issue of recognition of audio description as a dependent work and the requirements for the legal licence according to Art. 331 of the Polish Copyright and Related Rights Act. Finally, the author discusses the unsuccessful attempt to amend the Polish Cinematography Act in the field of audio description and proposes a return to the discontinued work.